Cellular and Molecular Mechanisms of Kidney Development: From the Embryo to the Kidney Organoid - Khoshdel Rad, Niloofar; Aghdami, Nasser; Moghadasali, Reza (Frontiers in Cell and Developmental Biology, 2020)
Development of the metanephric kidney is strongly dependent on complex signaling pathways and cell-cell communication between at least four major progenitor cell populations (ureteric bud, nephron, stromal and endothelial progenitors) in the nephrogenic zone. In recent years, the improvement of human-PSC-derived kidney organoids has opened new avenues of research on kidney development, physiology, and diseases. Moreover, the kidney organoids provide a three-dimensional (3D) in vitro model for the study of cell-cell and cell-matrix interactions in the developing kidney. In vitro re-creation of a higher-order and vascularized kidney with all of its complexity is a challenging issue; however, some progress has been made in the past decade. This review focuses on major signaling pathways and transcription factors that have been identified which coordinate cell fate determination required for kidney development. We discuss how extensive knowledge of these complex biological mechanisms translated into the dish, thus allowed the establishment of 3D human-PSC-derived kidney organoids.